The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1902/jop.1993.64.12.1199
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Healing in Relation to Radiographic Attachment and Endodontic Infection

Abstract: The aim of the present study was primarily to investigate if periodontal healing assessed by reduction in probing depth over time is significantly influenced by the initial degree of horizontal radiographic attachment loss and secondly to what degree any such relationship influenced the already established correlation between presence of a root canal infection and impaired marginal healing. The investigation was conducted as a retrospective study on 160 patients referred to a specialist periodontal clinic. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 11 publications
1
33
0
1
Order By: Relevance
“…Retrospective studies have already shown the influence of endodontic infection on the progression of marginal bone loss in periodontitis as well as on the healing process after scaling and root planing (6)(7)(8). Therefore, it is essential to recognize that pulp inflammation and necrosis may reflect negatively on the periodontium in terms of both the pathophysiological process and treatment response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective studies have already shown the influence of endodontic infection on the progression of marginal bone loss in periodontitis as well as on the healing process after scaling and root planing (6)(7)(8). Therefore, it is essential to recognize that pulp inflammation and necrosis may reflect negatively on the periodontium in terms of both the pathophysiological process and treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…However, this hypothesis lacks consistent evidence once it is based on the findings of a critical literature review (4) and on the microbiological evaluation of isolated clinical cases (5). Conversely, the effects of pulp disease on the periodontium are well documented (3,(6)(7)(8).…”
mentioning
confidence: 99%
“…If majority of bony support has been lost from periodontitis, regardless of predictability of endodontic therapy, tooth may have hopeless prognosis. Regeneration, root resection and hemisection are indicated as a part of strategic treatment of multirooted teeth [6,7]. In this case first endodontic therapy was performed then periodontal therapy & bonegrafting was done for periodontal regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies have suggested that patients with periodontal disease have a greater attachment loss if a root canal infection is also present. 22,23 Jaoui et al (1995) 24 evaluated 195 teeth in 35 patients with periodontitis who had received both endodontic and periodontal treatment and concluded that providing patients receive adequate supportive periodontal treatment, root canal treatment should not contribute to the risk of tooth loss for periodontal reasons. The importance of maintaining periodontal health is therefore critical to the long-term success of teeth that have been root canal treated and restored.…”
Section: Periodontal Evaluationmentioning
confidence: 99%